SULPHIDE-MINING IMPACTS IN THE PHYSICAL ENVIRONMENT: SIERRA DE CARTAGENA–LA UNIóN (SE SPAIN) CASE STUDY - Robles-Arenas V.M.; Rodríguez R.; García C.; Manteca J.I.; Candela L. (My University, 2006)
The environmental impact and potential-risk assessment of an abandoned sulphide-mining site in a semiarid climate is presented here, by the study case of Sierra de Cartagena–La Unión (SE Spain), a 2,500-year-old mining district extending over an area of 100 km2. The regional map illustrates the existence of 12 open-pits, 1,902 mining wells, 2,351 waste deposits, including 89 tailing dams and waste rock derived from mining processes. Mine wastes occupy an area of 9 km2 and have an approximate volume of 200 Mm3. Mineralogical, physical and chemical data distinguish nine different types of mine and metallurgical waste. According to the concentration of sulphate and heavy metals in sediment, soil, rainwater, surface water and groundwater samples, it is possible to conclude that the impact of mine activities occurs not only in the immediate mining area (100 km2), but also in the surrounding areas (an affected area of 1,000 km2 approximately). The hydrochemical data show that groundwater, runoff water and some rainwater samples exceed Spanish and European water quality guideline values for water supply. The main geochemical process recognised is sulphide-mineral oxidation and later-generated sulphate dissolution by groundwater and runoff. Runoff and wind are the major mechanisms of metals and sulphate transport in the study area and adjacent zones.
Keywords: MINE AND METALLURGICAL WASTE; ENVIRONMENTAL IMPACT AND RISK; MINE CLOSURE; SPAIN; SIERRA DE CARTAGENA-LA UNIóN